Analisis Perubahan Suhu Udara di Kota Medan Sebelum dan Sesudah Covid 19 Menggunakan Metode Statistika Quality Control - Wira Triono; Era Evalin Tampubolon; Yizhar Saputra Hondro (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Climate change has had a significant impact on various aspects of life, including air temperature in urban areas such as Medan City. This study aims to analyze changes in air temperature in Medan City during and after the COVID-19 pandemic, especially related to social restriction policies such as PPKM. Temperature data was obtained from UPT BMKG Medan for the period 2020 to 2025 and analyzed using I-MR (Individual-Moving Range), Cusum, and EWMA (Exponentially Weighted Moving Average) methods. The results of the analysis are expected to be able to show significant temperature differences as a result of the decline in human activities during the pandemic as well as the trend of post-pandemic temperature changes. This study is important as a basis for future environmental planning and climate change mitigation policies.